Efficient mRNA-Based Genetic Engineering of Human NK Cells with High-Affinity CD16 and CCR7 Augments Rituximab-Induced ADCC against Lymphoma and Targets NK Cell Migration toward the Lymph Node-Associated Chemokine CCL19 - Carlsten, Mattias; Levy, Emily; Karambelkar, Amrita; Li, Linhong; Reger, Robert; Berg, Maria; Peshwa, Madhusudan V.; Childs, Richard W. (Frontiers in Immunology, 2016)
For more than a decade, investigators have pursued methods to genetically engineer natural killer (NK) cells for use in clinical therapy against cancer. Despite considerable advances in viral transduction of hematopoietic stem cells and T cells, transduction efficiencies for NK cells have remained disappointingly low. Here, we show that NK cells can be genetically reprogramed efficiently using a cGMP-compliant mRNA electroporation method that induces rapid and reproducible transgene expression in nearly all transfected cells, without negatively influencing their viability, phenotype, and cytotoxic function. To study its potential therapeutic application, we used this approach to improve key aspects involved in efficient lymphoma targeting by adoptively infused ex vivo-expanded NK cells. Electroporation of NK cells with mRNA coding for the chemokine receptor CCR7 significantly promoted migration toward the lymph node-associated chemokine CCL19. Further, introduction of mRNA coding for the high-affinity antibody-binding receptor CD16 (CD16-158V) substantially augmented NK cell cytotoxicity against rituximab-coated lymphoma cells. Based on these data, we conclude that this approach can be utilized to genetically modify multiple modalities of NK cells in a highly efficient manner with the potential to improve multiple facets of their in vivo tumor targeting, thus, opening a new arena for the development of more efficacious adoptive NK cell-based cancer immunotherapies.